Calcium hydroxide diffusion after agitation of endodontic irrigants: an ex vivo study - Wakasugui, Lucas Takeo (2023)
Aim: To compare the influence of two methods of agitation of endodontics irrigants, by diffusion of calcium hydroxide [Ca(OH)2] through the dentinal tubules, measuring the pH of the medium where they were kept. Methods: Twenty mandibular incisors were prepared using a WaveOne Gold Large file, in a reciprocating movement, and then divided into (n = 10): gutta-percha cone (GPC) or Easy Clean system (ECS) agitation of 1% sodium hypochlorite and 17% ethylenediaminetetraacetic acid. The specimens were filled with Ca(OH)2 paste, placed in flasks with 4 mL of deionized water, and stored in an incubator. The pH was read using a digital pH meter immediately after storage (T0), after 7 (T1), 14 (T2), 21 (T3), and 35 (T4) days. Results: Statistical difference between groups was observed regardless of the day pH was measured (p < 0.01). From T2 on, ECS presented higher pH values in comparison with GPC, with significant difference (p < 0.01). Conclusion: Agitation of endodontic irrigants with ECS enhances the Ca(OH)2 diffusion, providing higher pH values, from the 14th day on, when compared with GPC.